Efeito de diferentes volumosos sobre a degradabilidade in situ de nutrientes e variáveis da fermentação ruminal, mediante a aplicação da somatotropina bovina - Sampaio, Alexandre Amstalden Moraes; Rossi Jr., Paulo; De Brito, Rodolfo Marques; Cestari, André Luis [UNESP]; Biondi, Alexandre [UNESP] (My University, 1998)
The objective of this work was to evaluate the effect of diets with different forages (sugarcane, corn silage, hydrolyzed bagasse and sugarcane + corn silage) on the ruminal fermentation and ruminal nutrients degradability, by the application of bovine somatotropin. Three bovines with ruminal cannulas were used in a factorial scheme (4 × 2). The pH, number of protozoa, ammonia and volatile fatty acids concentration were quantified. The potential and the effective degradability and degradation rate of dry matter and crude protein in each diet were evaluated, beyond gross energy disappearance. There were differences among diets on the effective degradability of dry matter and potential degradability, effective degradability and potentially degradable fraction of crude protein, being verified the same for the rBST application. There was effect of different forages on the variables of ruminal fermentation. The treatments did not affect the gross energy disappearance. The rBST application did not affect the variables of ruminal fermentation.
Effect of different forages on in situ degradability of nutrients and variables of ruminal fermentation, through the application of bovine somatotropin
Keywords: Bovine; Corn silage; Degradability; Hydrolyzed bagasse; Microorganisms; Ruminal fermentation; Somatotropin; Sugarcane